Becoming an Indonesian Muslim: The Idea of Religious Nationalism K.H. Ahmad Wahid Hasyim 1945-1953 - Z, Rijal Mumazziq; Rohmad, Ahmad Khubby Ali (DINIKA : Academic Journal of Islamic Studies, 2021)
This study aims to see the idea of religious nationalism K.H. A. Wahid Hasyim on Islam and Indonesia. K.H. A. Wahid Hasyim is an interesting figure in the midst of tug-of-war between the interests of making Indonesia an Islamic state and a secular state at the beginning of the founding of Indonesia, the idea of ​​KH. A. Wahid Hasyim became the middle ground. This study raises the main question, namely how the relationship between religion and the state according to K.H. Wahid Hasyim in the Indonesian context. This research is based on text reading and had analyzed by content analysis. This study concludes that KH. A. Wahid Hasyim is consistent in Islamic thought and prioritizes the unity and integrity of the nation. According to K.H. A. Wahid Hasyim, the state serves the religious needs of the people in accordance with the Pancasila basis. In matters of an individual nature (private), the government should not interfere. Meanwhile, the state may regulate issues of a social nature (public). Kiai Wahid is of the opinion that the secularistic relationship between religion and the state is only a theory, and has never actually happened. Islam still needs the state to protect the freedom of its citizens to practice their religion, while the state needs religious legitimacy to make a set of regulations in order to achieve benefit. Thoughts K.H. A. Wahid Hasyim belongs to the category of thinkers who relate religion and state as a mutualistic symbiotic relationship, where state and religion support each other. On the same dimension, its relevance lies in its idea of ​​prioritizing common interests over personal interests. Kiai Wahid's idea of​​religious nationalism is still relevant today. Especially in the context of maintaining the relationship between the state and religion, and giving the government a share to participate in efforts to facilitate its citizens in practicing their religion.